KUALITAS PELAYANAN BERDASARKAN PERMENDAGRI NOMOR 2 TAHUN 2017 TENTANG STANDAR PELAYANAN MINIMAL DI PELAYANAN DESA JARO KECAMATAN JARO KABUPATEN TABALONG (JAPB, 2022)
Quality of Service Based on Permendagri Number 2 of 2017 concerning Minimum Service Standards in Jaro Village Services, Jaro District, Tabalong Regency. The implementation of public services is an effort by the state to fulfill every citizen's basic needs and rights for goods, services, and administrative services provided by public service providers. Therefore, it is necessary to apply minimum service standards so the government can make it a benchmark and reference in providing services to the community. Minimum service standards, as regulated in Chapter I of the general provisions of Article I paragraph (17) of Law No.23 of 2014 concerning regional government, are provisions regarding the type and quality of essential services which are mandatory government affairs and are entitled to be obtained by every citizen at a minimum and minimum village service standards based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia number 2 of 2017 article 5 which includes: 1) provision and dissemination of service information, 2) provision of population and land data and information, 3) provision of certificates, 4) simplification of services, 5) and public complaints. The purpose of this study was to determine the extent of service quality at the Jaro village office based on the Minister of Home Affairs number 2 of 2017 regarding minimum service standards, Jaro District, Tabalong Regency. The type and approach of this research are descriptive–qualitative. The techniques used for data collection are observation, interviews, and documentation. Primary data sources were obtained from observations and interviews, while secondary data were obtained from the documentation. The data analysis method used is the analysis, according to Miles and Hubberman (2014). The results of this study indicate that the quality of service based on Permendagri Number 2 of 2017 at the Jaro Village Office, Jaro District, Tabalong Regency, is following Minimum Service Standards. Keywords: Service Quality, Minimum Service Standards, Permendagri Number 2 the Year 2017